Plasma glucose and thiocyanate response to different mixed cassava meals in non-diabetic Nigerians (1990)
We measured plasma glucose and thiocyanate levels before and up to 4 h after feeding 11 overnight fasted healthy non-diabetic volunteers randomly on three occasions each with three locally consumed cassava meals: (i) gari as eba 50 g; (ii) lafun 50 g and (iii) parboiled cassava flakes 76 g. Each of these meals contained 175 kcal (0.7 MJ) and was consumed with a sauce to a total caloric value of 300 kcal (1.26 MJ). On the fourth visit, each volunteer consumed 75 g glucose. While the peak and 2-h glucose values were greatest with oral glucose (P less than 0.01), they were similar with the three cassava meals, although tended to be lowest with lafirn. Similarly, areas (incremental and total) under the glucose/time curves were highest with oral glucose (P less than 0.05), but while eba and cassava flakes were similar, lafun had the lowest values (P less than 0.05). Plasma thiocyanate levels were unchanged after ingestion of oral glucose and eba, but increased to peak values (P less than 0.05) by 14 per cent on cassava flakes and by 23 per cent on lafun. We conclude that post-prandial glycaemia and plasma thiocyanate levels after cassava meals depend on the mode of preparation of the meal and that lafun showed the least glycaemic response of the three cassava meals tested although it caused the greatest increase in plasma thiocyanate levels. These findings suggest that a cyanogenetic potential does not always reflect a tendency to hyperglycaemia.